Advancing a system-level perspective in stakeholder theory: Insights from the institutional economics of John R. Commons - Vladislav Valentinov (Social Science Information, 2024)
Stakeholder theory is a growing body of scholarly literature at the crossroads of business ethics and strategic management. This literature encompasses two distinct levels of inquiry, the levels of the firm and of the capitalistic system as a whole. At the firm level, stakeholder theory provides insight into the roots of the firm-level competitive advantage, whereas at the system level, it explores how capitalistic business can act as a social institution serving moral goals. Until now, the firm-level and system-level perspectives in stakeholder theory have not been effectively integrated. Drawing on the classical institutional economics of John Commons, the present paper elaborates the distinction between the firm and system levels of stakeholder collaboration and examines how they are interconnected. Stakeholder collaboration is shown to be shaped by larger institutions, such as habits, customs, public purposes, and prevailing perceptions of reasonableness. Whereas the system-level perspective in stakeholder theory focuses on the evolution of these larger institutions, the firm-level perspective explores how these institutions contribute to the emergence of the firm-level competitive advantage, thereby generating evolutionary forces that adjust the larger institutions. – – La théorie des parties prenantes est un corpus de plus en plus important d'ouvrages scientifiques au carrefour de l'éthique des affaires et de la gestion stratégique. Cette littérature englobe deux niveaux distincts d'enquête, celui de l'entreprise et celui du système capitaliste dans son ensemble. Au niveau de l'entreprise, la théorie des parties prenantes permet de comprendre les racines de l'avantage concurrentiel de l'entreprise, tandis qu'au niveau du système, elle explore la manière dont l'entreprise capitaliste peut agir en tant qu'institution sociale au service d'objectifs moraux. Jusqu'à présent, les perspectives au niveau de l'entreprise et au niveau du système dans la théorie des parties prenantes n'ont pas été intégrées de manière efficace. S'inspirant de l'économie institutionnelle classique de John Commons, le présent document élabore la distinction entre les niveaux entreprise et système de la collaboration des parties prenantes et examine la manière dont ils sont interconnectés. Il est démontré que la collaboration entre les parties prenantes est façonnée par des institutions plus vastes, telles que les habitudes, les coutumes, les objectifs publics et les perceptions dominantes du caractère raisonnable. Alors que la perspective systémique de la théorie des parties prenantes se concentre sur l'évolution de ces institutions plus vastes, la perspective au niveau de l'entreprise explore la manière dont ces institutions contribuent à l'émergence d'un avantage concurrentiel au niveau de l'entreprise, générant ainsi des forces évolutives qui ajustent les institutions plus vastes.
Keywords: 330; classical institutional economics; firm-level perspective; John R. Commons; stakeholder theory; system-level perspective; économie institutionnelle classique; théorie des parties prenantes; perspective au niveau de l'entreprise; perspective au niveau du système